1985
DOI: 10.1084/jem.161.6.1384
|View full text |Cite
|
Sign up to set email alerts
|

Size variation of the M protein in group A streptococci.

Abstract: Streptococcal M protein, the fibrillar molecule on the surface of the group A streptococcus, is considered to be one of the major factors responsible for the ability of this human pathogen to cause disease (1). Though type-specific opsonic antibodies directed towards the M molecule enable the infected host to clear the invading streptococcus (1, 2), the ability of this organism to vary its antigenic structure has probably been the major factor responsible for its survival. To date, over 75 serologically differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
89
2

Year Published

1988
1988
2007
2007

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 128 publications
(92 citation statements)
references
References 36 publications
1
89
2
Order By: Relevance
“…PG-associated OMPs would be released by lysozyme treatment, with one, two, etc., murein subunits remaining attached, giving them an increasingly lower electrophoretic mobility. Similar phenomena have also been described for other Gram-negative bacteria, including Braun's lipoprotein of E. coli (Wensink & Witholt,198 1) and the major OMPs of Rhizobium leguminosarum (de Maagd et al, 1989a, b) and Legionella pneumophila (Butler & Hoffman, 1990) and for the M protein of group A streptococci (Fischetti et al, 1985;Pancholi & Fischetti, 1988). The high-molecular-mass bands in immunoblots of lysozyme-treated sonicated cell extracts, ranging from 50 to 54 kDa reacting with the anti-25-27 kDa mAb, 54 to 66 kDa with the anti-31-34 kDa mAb and 78 kDa with the anti-36-38 kDa mAb, probably represent dimeric forms of each major OMP where the monomers are linked together by PG.…”
Section: Discussionmentioning
confidence: 61%
“…PG-associated OMPs would be released by lysozyme treatment, with one, two, etc., murein subunits remaining attached, giving them an increasingly lower electrophoretic mobility. Similar phenomena have also been described for other Gram-negative bacteria, including Braun's lipoprotein of E. coli (Wensink & Witholt,198 1) and the major OMPs of Rhizobium leguminosarum (de Maagd et al, 1989a, b) and Legionella pneumophila (Butler & Hoffman, 1990) and for the M protein of group A streptococci (Fischetti et al, 1985;Pancholi & Fischetti, 1988). The high-molecular-mass bands in immunoblots of lysozyme-treated sonicated cell extracts, ranging from 50 to 54 kDa reacting with the anti-25-27 kDa mAb, 54 to 66 kDa with the anti-31-34 kDa mAb and 78 kDa with the anti-36-38 kDa mAb, probably represent dimeric forms of each major OMP where the monomers are linked together by PG.…”
Section: Discussionmentioning
confidence: 61%
“…E. coli DH5a was grown in Luria broth (32) or tryptone (32), and S. pyogenes strains were grown in ToddHewitt broth supplemented with 0.2% yeast extract (THY) (11). Antibiotics were used at the following concentrations: ampicillin (Ap) at 50 ,ug/ml, chloramphenicol (Cm) at 10 ,ug/ml for E. coli and 5 ,ug/ml for S. pyogenes, kanamycin (Km) at 25 ,ug/ml for E. coli and 200 ,ug/ml for S. pyogenes, and streptomycin at 1,000 ,ug/ml for S. pyogenes.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, this enzyme has been used as a molecular tool for decades to isolate cell-wall-linked proteins and extract DNA from group A streptococci (9,10). More recently, we have shown that the bacteriolytic properties of PlyC can protect mice from streptococcal challenge, suggesting a therapeutic use of the enzyme (11).…”
mentioning
confidence: 99%